The equation of state of a cell fluid model in the supercritical region - Kozlovskii, M.P.; Pylyuk, I.V.; Dobush, O.A. (Condensed Matter Physics, 2018)
The analytic method for deriving the equation of state of a cell fluid model in the region above the critical temperature (T > Tc) is elaborated using the renormalization group transformation in the collective variables set. Mathematical description with allowance for non-Gaussian fluctuations of the order parameter is performed in the vicinity of the critical point on the basis of the ρ⁴ model. The proposed method of calculation of the grand partition function allows one to obtain the equation for the critical temperature of the fluid model in addition to universal quantities such as critical exponents of the correlation length. The isothermal compressibility is plotted as a function of density. The line of extrema of the compressibility in the supercritical region is also represented.